The effects of heat shock on the morphology and protein synthesis of the epidermis of Xenopus laevis larvae (The Rockefeller University Press, 1988)
By scanning electron microscopy, we have observed that a 20-min heat shock at 37 degrees C, although not lethal, causes extensive damage to the epidermis of 30-h and 2-d (post-fertilization) Xenopus laevis larvae. The primary effects of heat shock are the apical swelling of the epidermal cells, giving the epidermis a "cobblestone" appearance, and the selective shedding of the ciliated cells. The shed cells may be cell fragments, however, because some of them are anucleate. Shed cells also exhibit the enriched synthesis of a group of heat shock proteins of 62,000 D molecular weight, suggesting that these proteins are specific to the shed cells. Prolonged heat shock of these larvae (i.e., 30 min at 37 degrees C) results in the complete disintegration of the epidermis, followed by larval death. At later stages of development (3- d and 4-d post-fertilization), the epidermis becomes more resistant to heat-induced damage inflicted by a 20-min heat shock. This increase in resistance coincides with the development of large secretory cells and the loss of ciliated cells in the epidermis and thus parallels a change in the state of histological differentiation.